2020
DOI: 10.1002/ijfe.1851
|View full text |Cite
|
Sign up to set email alerts
|

Market efficiency and volatility persistence of cryptocurrency during pre‐ and post‐crash periods of Bitcoin: Evidence based on fractional integration

Abstract: This paper investigates both market efficiency and volatility persistence in 12 cryptocurrencies during pre-crash and post-crash periods. We were motivated by the erroneous belief of some authors that driving currency, Bitcoin is inefficient. By considering robust fractional integration methods in linear and nonlinear set up, we found that markets of Bitcoin and most altcoins considered in our samples can be dubbed as efficient, and these are highly volatile particularly in the post-crash sample that we are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…This is denoted the Adaptive Market Hypothesis (AMH). Urquhart and Hudson (2013), , Noda (2016), Ito et al (2016), Urquhart and McGroarty (2016) and Yaya et al (2019) investigates the market efficiency with methods derived with the AMH. Furthermore, Chu et al (2019) investigates the AMH for the two largest cryptocurrencies, and found evidence that supports the hypothesis of a time varying market efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is denoted the Adaptive Market Hypothesis (AMH). Urquhart and Hudson (2013), , Noda (2016), Ito et al (2016), Urquhart and McGroarty (2016) and Yaya et al (2019) investigates the market efficiency with methods derived with the AMH. Furthermore, Chu et al (2019) investigates the AMH for the two largest cryptocurrencies, and found evidence that supports the hypothesis of a time varying market efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Blockchain is a new digital technology which could change the way industries and organizations around the world are organized and structured [1]. Blockchain has prompted many companies and organizations, as well as political powers, to rethink the marketing strategies and tactics for their products and services [2,3]. Blockchain technology came about with the creation of the cryptocurrency known as Bitcoin.…”
Section: Introductionmentioning
confidence: 99%
“…Bitcoin is a cryptocurrency based on a peer-to-peer payment system [4]. Although, in recent years, some publications have addressed Bitcoin and blockchain as one in the same technology, the fact is that Bitcoin is merely one application of the emerging digital technology known as blockchain [3,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The general consensus derived from literature is that Bitcoin is only market (in)efficient over certain time periods (i.e. time-varying efficiency), as insinuated by the adaptive market hypothesis (AMH) of Lo ( 2004 ), although these studies identify different time periods or structural break points when the Bitcoin market switches from being inefficient to market efficient or vice versa (Urquhart, 2016 ; Nadarajah & Chu, 2017 ; Bariviera et al, 2017 ; Bariviera, 2017 ; Tiwari et al, 2018 ; Jiang et al, 2018 , Alvarez-Ramirez et al, 2018 ; Zhang et al, 2018 ; Vidal-Tomas et al, 2018 ; Khuntia & Pattanayak 2018 ; Aggarwal, 2019 ; Chu et al, 2019 ; Sensoy, 2019 ; Tran & Leirvik, 2020 ; Vidal-Tomas, 2020 ; Wu & Chen, 2020 ; Lopez-Martin et al, 2021 ; Manahov & Urquhart, 2021 ; Yaya et al, 2021 ). There also exists a smaller and more recent strand of studies (Corbet & Paraskei, 2020 ; Naeem et al, 2021 ) which identify a different mechanism for asymmetric behavior in the Bitcoin returns in which market efficiency switches between bear and bulls markets.…”
Section: Introductionmentioning
confidence: 99%